Antioxidants and antioxidant activity of several pigmented rice brans - Thunnop Laokuldilok (2018)
This study investigated the antioxidant content and activity of phenolic acids, anthocyanins, α-tocopherol and γ-oryzanol in pigmented rice (black and red rice) brans. After methanolic extraction, the DPPH free radical scavenging activity and antioxidant activity were measured. The pigmented rice bran extract had a greater reducing power than a normal rice bran extract from a long grain white rice. All bran extracts were highly effective in inhibiting linoleic acid peroxidation (60-85%). High-performance liquid chromatography (HPLC) analysis of antioxidants in rice bran found that γ-oryzanol (39-63%) and phenolic acids (33-43%) were the major antioxidants in all bran samples, and black rice bran also contained anthocyanins 18-26%. HPLC analysis of anthocyanins showed that pigmented bran was rich in cyanidin-3-glucoside (58-95%). Ferulic acid was the dominant phenolic acid in the rice bran samples. Black rice bran contained gallic, hydroxybenzoic, and protocatechuic acids in higher contents than red rice bran and normal rice bran. Furthermore, the addition of 5% black rice bran to wheat flour used for making bread produced a marked increase in the free radical scavenging and antioxidant activity compared to a control bread. © 2010 American Chemical Society.